A comparative study of mouse bone marrow mesenchymal stem cells isolated using three easy‐to‐perform approaches. Issue 12 (17th October 2022) - Lu, Yalan; Han, Yunlin; Zhou, Li; Shi, Guiying; Bai, Lin; Wang, Kewei; Qin, Chuan
Abstract : Mouse bone marrow mesenchymal stem cells (mBM‐MSCs) are important for preclinical tissue regeneration and repair studies. In the present study, we isolated mBM‐MSCs using three easy‐to‐perform methods (whole bone marrow‐adherent culture, density‐gradient centrifugation, and bone digestion), and then compared the morphology, proliferation, differentiation, and paracrine factor profiles of the isolated mBM‐MSCs. Of these three isolation methods, the bone digestion method resulted in the highest quantity of mBM‐MSCs with high growth potential and moderate differentiation. Conversely, the mBM‐MSCs isolated through the whole bone marrow‐adherent method exhibited the lowest potency for proliferation and differentiation. The differentially expressed factors between mBM‐MSCs were primarily those involved in immune responses. The highly expressed secreted factors included cytokines/members of the chemokine family, growth factors, and protein binding/proteinase activity. These findings provide a fundamental reference for development of MSC isolation methods. Abstract : Mouse BM‐MSCs were isolated using three easy‐to‐perform methods [whole bone marrow‐adherent culture (BM‐MSC‐A), density‐gradient centrifugation (BM‐MSC‐G), and bone digestion (BM‐MSC‐D)]. BM‐MSC‐D exhibited the highest quantity of mBM‐MSCs with high growth potential and moderate differentiation. The BM‐MSC‐A showed the lowest potency for proliferation and differentiation. The paracrine factors were mainly involved in chemokine family, growth factors,  and protein binding/proteinase activity.